Revealing the cryptic diversity of the widespread and poorly known South American blind snake genus Amerotyphlops (Typhlopidae: Scolecophidia) through integrative taxonomy - Graboski, Roberta [UNESP] (2022)
Morphological stasis is generally associated with relative constancy in ecological pressures throughout time, producing strong stabilizing selection that retains similar shared morphology. Although climate and vegetation are commonly the main key factors driving diversity and phenotypic diversification in terrestrial vertebrates, fossorial organisms have their morphology mostly defined by their fossorial lifestyle. Among these secretive fossorial organisms, blind snakes of the South American genus Amerotyphlops are considered poorly studied when compared to other taxa. Here, we evaluate the cryptic diversity of Amerotyphlops using phylogenetic and multivariate approaches. We based our phylogenetic analysis on a molecular dataset composed of 12 gene fragments (eight nuclear and four mitochondrial) for 109 species of Typhlopidae. The multivariate analysis was implemented using 36 morphological variables for 377 specimens of Amerotyphlops. Additionally, we contrast our phylogenetic result with the morphological variation found in cranial, external and hemipenial traits. Our phylogenetic results recovered with strong support the following monophyletic groups within Amerotyphlops: (1) a clade formed by A. tasymicris and A. minuisquamus; (2) a clade composed of A. reticulatus; (3) a north-eastern Brazilian clade including A. yonenagae, A. arenensis, A. paucisquamus and A. amoipira; and (4) a clade composed of A. brongersmianus and a complex of cryptic species. Based on these results we describe four new species of Amerotyphlops from north-eastern and south-eastern Brazil, which can be distinguished from the morphologically similar species, A. brongersmianus and A. arenensis.